Subnational Administration in Afghanistan, Volume 1. Assessment and Recommendations for Action - World Bank (Washington, DC, 2013)
This report proposes a two-pronged strategy of government action for securing progress in sub-national administration, using the structures, and discipline that form the distinctive heritage of the Afghan state. One strand calls for the center to commit itself to delivering some basic support for provinces, districts, and provincial municipalities, in their functional role as service provider or commissioner, and in their political role as local representative of the unitary state. The second strand of the strategy is comprised of tailored incentives for sub-national administrations, that reflect their institutional and historical roots. The task is to make this de-concentrated system work, through effective incentives at the sub-national level that will entail the provision of valued resources that are triggered by simple measures of administrative effort, not performance, and tailoring the incentives to suit the specific situation of the administration, with distinct differences between the incentives provided to provinces, districts, and provincial municipalities. To this end, the report proposes unconditional commitments from the Government in Kabul to: complete the pension reform, i.e., build, and strengthen capacity within the central administration entities, increasing Treasury authority, and establishing procedures to strengthen the budgetary process. Likewise, it proposes to restore provincial infrastructure, and priority support for provincial health and education departments. By designing specific project support, it is intended to help shift the focus towards pro-province and pro-service delivery objectives.